Whole exome sequencing reveals the maintained polyclonal nature from primary to metastatic malignant peripheral nerve sheath tumor in two patients with NF1. (10th September 2019) - Godec, Abigail; Jayasinghe, Reyka; Chrisinger, John S A; Prudner, Bethany; Ball, Tyler; Wang, Yuxi; Srihari, Divya; Kaushal, Madhurima; Dietz, Hilary; Zhang, Xiaochun; Pekmezci, Melike; Dahiya, Sonika; et al.
Abstract: Background: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive soft tissue sarcomas with high metastatic rates and poor overall patient survival. There are currently no effective therapies, underscoring the pressing need to define the molecular etiologies that underlie MPNST progression. The aim of this study was to examine clonal progression and identify the molecular events critical for MPNST spread. Methods: In two patients with temporally and spatially distinct metastatic lesions, we employed whole exome sequencing (WES) to elucidate the genetic events of clonal progression, thus identifying the molecular events critical for MPNST spread. Results: First, we demonstrated shared clonal origins for the metastatic lesions relative to the primary tumors, which were maintained throughout the course of MPNST progression, supporting the conclusion that cancer cells with metastatic potential already exist in the primary neoplasm. Second, we discovered TRIM23, a member of the Tripartite Motif family of proteins, as a regulator of MPNST lung metastatic spread in vivo. Conclusions: The ability to track the genomic evolution from primary to metastatic MPNST offers new insights into the sequence of genetic events required for tumor progression and has identified TRIM23 as a novel target for future study in this rare cancer.